2015
DOI: 10.1037/neu0000188
|View full text |Cite
|
Sign up to set email alerts
|

Impaired recognition of faces and objects in dyslexia: Evidence for ventral stream dysfunction?

Abstract: The difficulty that people with dyslexia experience with reading might be the most salient manifestation of a more general high-level visual deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
73
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 100 publications
9
73
2
Order By: Relevance
“…Sigurdardottir et al, 2015). This suggests that, in dyslexia, the general capacity for perceptual processes to establish short-term representations of stimulus consistency may be impaired (Ahissar et al, 2006; Chandrasekaran et al, 2009; Hornickel and Kraus, 2013; Jaffe-Dax et al, 2015; Oganian and Ahissar, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sigurdardottir et al, 2015). This suggests that, in dyslexia, the general capacity for perceptual processes to establish short-term representations of stimulus consistency may be impaired (Ahissar et al, 2006; Chandrasekaran et al, 2009; Hornickel and Kraus, 2013; Jaffe-Dax et al, 2015; Oganian and Ahissar, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Their task involved visual statistical learning of relationships between complex visual objects (cartoon aliens), but as our previous research shows that reading problems are associated with poor recognition of such complex visual objects 51 , their finding may reflect suboptimal visual processing of the individual items themselves, but recognition of individual items was not tested. The rapid serial visual presentation used is also of some concern given reports that reading problems are associated with a processing deficit for rapidly presented stimuli 82 .…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the tasks on which this conclusion is based, such as the detection of high-pass filtered rings 48 , detection of fixed sinewave gratings 49 , or the sensitivity to static visual form coherence 50 , might mainly tap into the workings of the lower portion of the ventral visual stream. We have previously demonstrated that people with dyslexia are impaired not only at recognizing visually presented words but also faces and other visually complex objects 51 . While we emphasize that this does not automatically argue against other theories of the causes of dyslexia, the possibility remains that reading problems in dyslexia might in some ways be a manifestation of a more general high-level visual deficit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for a concurrent impairment in face perception is provided by the finding that a well-characterized group of DD adults performed significantly more poorly compared with controls (Sigurdardottir, Ívarsson, Kristinsdóttir, & Kristjánsson, 2015) on the Cambridge Face Memory Test (Duchaine & Nakayama, 2006). Similarly, relative to controls, DD individuals matched faces more slowly, showed disproportionate cost in performance when target and distractor faces differed in viewpoint, and discriminated faces more poorly, particularly as the faces were increasingly alike perceptually (Gabay, Dundas, Plaut & Behrmann, 2017).…”
Section: Introductionmentioning
confidence: 99%